Supervisi Pendidikan dalam Peningkatan Mutu Pendidikan di Sekolah - I Made Ariasa Giri (UHN IGB Sugriwa Denpasar, 2016)
Supervision is imperative for the improvement of the school education quality. In doing a supervision the supervisor should pay attention to the process, effectiveness, the system, the information,the evaluation, the principles, the programs, and the objectives, and the clinical model.